Pengaruh Waktu Fertilisasi dan Sistem Inkubasi yang Berbeda terhadap Tingkat Fertilisasi Sapi Lokal Secara In Vitro - F. L. Syaiful; R. Saladin; Jaswandi Jaswandi; Z. Udin (Universitas Andalas, 2011)
The purpose of this study was to determine the effect of fertilization time and different incubation systems on fertilization level by in-vitro. The mature of ovaries from indigenous cow and fresh cement from Holstein Frisian cows (FH), 0.9 % NaCl physiological PBS, Nissui Japan, l,TCM-199, HEPES 30 μM, 20 mL Heparin, 10% goat serum, 250 g/ml FSH BO medium, mediumgentamisain 50 mB-O, mineral oil, alcohol, aquabidest, and 1% aceto orcein were materials and reagents. The Completely Randomized Design (CRD) in factorial pattern was used. Results shown no significant effect on the percentage of fertilized oocytes and level of development of pronuclei (2PN and> 2PN) by different timing of fertilization and incubation system. The development of pronucleus (1PN) showed significant (P <0.05) on 12 hours (37.60 %), but no significant effect on different incubation system. It concluded, the system of incubation and time of fertilization has no effect on oocyte fertilization rate. Oocytes fertilization time can be performed at 6 hours, 12 hours, and 18 hours, while the extension of the period of fertilization until 18 hours did not increase the level of fertilization.